2015
DOI: 10.1002/rcm.7116
|View full text |Cite
|
Sign up to set email alerts
|

The complexity and structural diversity of ant venom peptidomes is revealed by mass spectrometry profiling

Abstract: The biochemical complexity of ant venoms, associated with an enormous ecological and taxonomic diversity, suggests that stinging ant venoms constitute a promising source of bioactive molecules that could be exploited in the search for novel drug and biopesticide leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 64 publications
13
45
0
1
Order By: Relevance
“…The number of species within each subfamily ranges from 1 to more than 6000 2 . Of these subfamilies, 13 comprise ants that employ a stinger to inject a peptide-rich venom used for predation, defence and communication [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The number of species within each subfamily ranges from 1 to more than 6000 2 . Of these subfamilies, 13 comprise ants that employ a stinger to inject a peptide-rich venom used for predation, defence and communication [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…As they have been little studied, ant venom peptides represent a potentially promising source of bioactive molecules with novel scaffolds and original pharmacological activities. Previous studies (Aili et al 2014;Touchard et al 2014;Touchard et al 2015) have demonstrated that the venoms of stinging ants are mostly comprised of small peptides, similarly to spider, scorpion and cone snail venoms. A limited number of peptidic toxins from several ant subfamilies such as the Ponerinae (Cologna et al 2013;Johnson et al 2010;Orivel et al 2001), Paraponerinae (Piek et al 1991), Ectatomminae (Arseniev et al 1994;Pluzhnikov et al 2000), Myrmicinae (Rifflet et al 2012), Myrmeciinae (Inagaki et al 2004;Inagaki et al 2008) and Pseudomyrmecinae (Pan and Hink 2000) have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…This is well illustrated in scorpions where scorpions with more potent venom possess relatively slender claws (Van der Meijden, Herrel & Summers, 2010). Although little data on the potency and the toxicity of ant venoms are available, both A. horridus and A. emarginatus have unusual venom compositions that vastly contrast with venoms of Odontomachus and other ponerine ants (Touchard et al, 2015). Furthermore, the investigation of the A. emarginatus venom resulted in the discovery of a novel family of neurotoxins that reversibly paralyses insects (Touchard et al, 2016).…”
Section: Influence Of Physiology On Strike Performancementioning
confidence: 99%